2022
DOI: 10.3389/fimmu.2022.841107
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Derived Natural Killer Cell Therapies - Expansion and Targeting

Abstract: Treatment of cancer with allogeneic natural killer (NK) cell therapies has seen rapid development, especially use against hematologic malignancies. Clinical trials of NK cell-based adoptive transfer to treat relapsed or refractory malignancies have used peripheral blood, umbilical cord blood and pluripotent stem cell-derived NK cells, with each approach undergoing continued clinical development. Improving the potency of these therapies relies on genetic modifications to improve tumor targeting and to enhance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 153 publications
(201 reference statements)
0
33
0
Order By: Relevance
“…PB-derived NK cells can be easily provided, and require activation and expansion, but the yield could be affected by donor variability. IPSCs can be maintained in an undifferentiated state and grown indefinitely, therefore enabling the production of huge numbers of homogeneous NK cells providing a base for a standardized, off-the-shelf approach [ 123 , 124 , 125 ].…”
Section: Adoptive Transfer Of Nk Cellsmentioning
confidence: 99%
“…PB-derived NK cells can be easily provided, and require activation and expansion, but the yield could be affected by donor variability. IPSCs can be maintained in an undifferentiated state and grown indefinitely, therefore enabling the production of huge numbers of homogeneous NK cells providing a base for a standardized, off-the-shelf approach [ 123 , 124 , 125 ].…”
Section: Adoptive Transfer Of Nk Cellsmentioning
confidence: 99%
“…UCB can also be a source of human iPSCs, which represent an alternative to produce NK cells in a standardized manner for anticancer immunotherapy [ 157 ]. Indeed, iPSCs can be obtained through the genetic reprogramming of various somatic cell types by induced overexpression of different stemness transcription factors, usually represented by Oct, Sox2, Klf4, and c-Myc [ 158 ].…”
Section: The Challenge Of Designing Ucb-derived Nk Cell Adoptive Therapymentioning
confidence: 99%
“…The irradiation limits their ability to expand and persist in vivo, reducing antitumor efficacy [ 92 ]. Preclinical studies and clinical trials of cell therapy have shown that improved CAR-T cell persistence leads to better therapeutic efficacy [ 93 , 94 ]. Similar studies on NK cells have also shown that persistence in preclinical in vivo models correlates with better tumor killing ability [ 67 ].…”
Section: Source and Preparation Of Nk Or Car-nk Cells For Clinical Usementioning
confidence: 99%